Quantum mechanical modeling of excited electronic states and their relationship to cathodoluminescence of BaZrO3 - Moreira, Mário L. [UNESP]; Andrés, Juan; Gracia, Lourdes; Beltrán, Armando; Montoro, Luciano A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (AIP Publishing, 2013)
First-principles calculations set the comprehension over performance of novel cathodoluminescence (CL) properties of BaZrO3 prepared through microwave-assisted hydrothermal. Ground (singlet, s*) and excited (singlet s** and triplet t**) electronic states were built from zirconium displacement of 0.2 Å in {001} direction. Each ground and excited states were characterized by the correlation of their corresponding geometry with electronic structures and Raman vibrational frequencies which were also identified experimentally. A kind of optical polarization switching was identified by the redistribution of 4dz2 and 4dxz (Zr) orbitals and 2pz O orbital. As a consequence, asymmetric bending and stretching modes theoretically obtained reveal a direct dependence with their polyhedral intracluster and/or extracluster ZrO6 distortions with electronic structure. Then, CL of the as-synthesized BaZrO3 can be interpreted as a result of stable triplet excited states, which are able to trap electrons, delaying the emission process due to spin multiplicity changes. © 2013 AIP Publishing LLC.
Keywords: Asymmetric bending; Excited electronic state; First-principles calculation; Microwave-assisted hydrothermal; Optical polarization switching; Quantum mechanical model; Spin multiplicity; Stretching modes; Calculations; Cathodoluminescence; Electronic states; Electronic structure; Excited states; Quantum theory; Zirconium; Barium compounds